The Ethnography Study of Tablighi Jamaat’s Da’wah Communication in the Symbolic Interactionism Perspective - Joni Rusdiana; Prahastiwi Utari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This article aims to see how the three premises of Blumer's Symbolic Interactionism are able to explain thephenomenon of the Tablighi Jamaat preaching in the form of khuruj and jaulah. The question to be answeredin this article is how Tablighi Jamaat interprets the concept of da'wah (preaching), how the meaningconstructed and how the meaning maintained or modified. Using the ethnographic method, this study looks athow the three premises of Blumer Symbolic Interactionism work. Based on the findings and results of theanalysis, it was found that the construction of the meaning of da'wah in the Tablighi Jamaah was very differentfrom the general understanding of the community. According to the Tablighi Jamaat, da’wah is not a lecturebut invites others to obey the rules of Islam. The main purpose of da'wah according to the Tablighi Jamaat isnot to improve others but to improve themselves and is obligatory for every Muslim. This series of meaningfulconstructs has been built since the beginning of this movement, started by Maulana Ilyas. Long beforeMaulana Ilyas chose and maintained the madrasa as a method of da'wah while continuing to evaluate it tothe conclusion that madrasas were not the right solution to improve society as a whole. Furthermore, he appliedthe methods of da'wah and tabligh which he obtained not from social interaction, but obtained from God'sinspired inspiration. Thus, in this phenomenon, the perspective of Blumer Symbolic Interactionism seems tobe limited and unable to explain it thoroughly.